Genetics Meets Metabolomics from Experiment to Systems Biology - Suhre, Karsten (Springer New York : Imprint: Springer, 2012)
Unlike previous books published on metabolomics, this book switches the focus from experimental questions and technical challenges, to the application of metabolomics with an emphasis on the underlying genetics. The chapters provide a thorough basis for the understanding of the underlying experimental techniques, concepts and potential biomedical applications of this exciting field. The interdisciplinary approach of this book addresses a wide readership, and contains educational aids for anyone not familiar with a particular area of metabolomics. The area of research where genetics and metabolomics meet is likely to represent a field where systems biology shall prosper highly in the years to come.